JAK INHIBITORS IN ATOPIC DERMATITIS: CURRENT EVIDENCE AND CLINICAL APPLICATIONS – A NARRATIVE REVIEW - Stankowska, Patrycja; Ilkiv, Ivanna; Adler, Konrad; Gebert , Zuzanna; Kucharska, Agata; Dłużewska, Magdalena; Zaręba, Agnieszka; Juszkiewicz, Dawid; Kiełczewski, Krzysztof; Fetner, Barbara (International Journal of Innovative Technologies in Social Science, 2026)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by epidermal barrier dysfunction, immune dysregulation, and severe pruritus that significantly impairs quality of life. In recent years, Janus kinase (JAK) inhibitors have emerged as an important therapeutic option for patients with moderate-to-severe AD due to their rapid onset of action and ability to inhibit multiple cytokine pathways involved in disease pathogenesis. This narrative review summarizes the current evidence regarding the mechanism of action, clinical efficacy, safety profile, and practical use of JAK inhibitors in AD. A literature search of recent clinical trials, systematic reviews, meta-analyses, and international guidelines was performed using PubMed, Scopus, and major dermatological journals. Available evidence demonstrates that selective JAK1 inhibitors such as upadacitinib and abrocitinib provide rapid reduction of pruritus and significant improvement in Eczema Area and Severity Index (EASI) scores. Baricitinib has also shown clinical benefit in selected patient populations. Despite strong efficacy, treatment with JAK inhibitors requires careful patient selection and monitoring because of potential risks including infections, laboratory abnormalities, cardiovascular events, and thromboembolic complications. Current evidence supports JAK inhibitors as valuable systemic therapies for patients with moderate-to-severe AD, particularly when rapid disease control is required. Long-term studies and real-world evidence remain essential for further optimization of treatment strategies and safety assessment.